Kedudukan Harta Waris Hasil Isbat Nikah Bagi Pasangan yang Sudah Meninggal di Pengadilan Agama Surabaya (Studi Kasus Penetapan Nomor 2735/Pdt.P/2020/PA.Sby) - Aliffatul Alfiah; Aris Nurullah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Marriage in Islam has been discussed a lot, starting from how to find the criteria for a potential life partner, how to apply for a marriage contract, to how to treat them when they officially become life partners. However, one thing that is not clearly regulated in the Koran is marriage registration. The most important thing to be investigated in this work is the judge's report regarding the marriage certificate of a deceased partner being registered and reported in a case study at the Surabaya Religious Court from an Islamic law perspective regarding the position of marriage isbat for a deceased partner. The aim of this research is also to expand and deepen knowledge, especially in the development of Islamic legal knowledge regarding the position of inheritance of inheritance resulting from marriage isbat for deceased couples at the Surabaya Religious Court (Case study determination number 2735/Pdt.P/2020/PA.SBY). This research is qualitative research with a juridical and psychological approach. Data was collected through observation, interviews and documentation. The results of the research show that the position of inheritance resulting from the isbat marriage of a deceased partner can be claimed in time to fulfill formal or substantive requirements when filing a case in the Religious Court and proof that the marriage is real. If the conditions and terms of marriage are met then the judge must grant it.